2015
DOI: 10.1128/aac.03947-14
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Nitazoxanide with Neuraminidase Inhibitors against Influenza A Viruses In Vitro

Abstract: The emergence of drug-resistant influenza A virus (IAV) strains represents a serious threat to global human health and underscores the need for novel approaches to anti-influenza chemotherapy. Combination therapy with drugs affecting different IAV targets represents an attractive option for influenza treatment. We have previously shown that the thiazolide anti-infective nitazoxanide (NTZ) inhibits H1N1 IAV replication by selectively blocking viral hemagglutinin maturation. Herein we investigate the anti-influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 38 publications
(54 reference statements)
0
65
0
1
Order By: Relevance
“…Indeed, both in vitro and in the clinical trials referred to [20,34] a good synergy between nitazoxanide and oseltamivir is observed, and the lack of direct action against viral RNA or protein should lessen the development of resistance. In support of this, we note that in the case of hepatitis C as well as IAV (PR8 strain) it was shown [40,41] that generation of resistant strains was not observed following challenge with nitazoxanide; indeed susceptibility toward other directly acting antivirals was unaffected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, both in vitro and in the clinical trials referred to [20,34] a good synergy between nitazoxanide and oseltamivir is observed, and the lack of direct action against viral RNA or protein should lessen the development of resistance. In support of this, we note that in the case of hepatitis C as well as IAV (PR8 strain) it was shown [40,41] that generation of resistant strains was not observed following challenge with nitazoxanide; indeed susceptibility toward other directly acting antivirals was unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent publication [20], in addition to the hemagglutinin titration assay, two independent viral titres were used to measure the potency of nitazoxanide; namely a plaque assay and a TCID 50 infectivity assay, using confluent MDCK monolayers in both cases. The A/Puerto Rico/8/1934(H1N1) strain of IAV was used in all cases.…”
Section: Antiviral Assaysmentioning
confidence: 99%
“…It also showed no effect on cardiac repolarization in a clinical trial for cardiac safety. 69 In recent studies, 32 was revealed as a promising antiviral agent against a wide range of pathogenic viruses including influenza virus, 70 HBV, 71 HCV, 71 EBOV, 72 DENV, 73 JEV, 74 HIV, 75 and ZIKV, 76 among others with IC 50 values ranging from 0.06 to 1.0 μg/mL 77,78 Its mechanism studies revealed that multiple host antiviral pathways were involved, and as such 32 is widely known as a polypharmacology antiviral agent. 32 activated protein kinase R (PKR), which plays vital roles in innate immune system.…”
Section: Eukaryotic Initiation Factor 2αmentioning
confidence: 99%
“…In vitro studies have identified that NTZ/TIZ has antiviral activity against a range of different influenza A (H1, H3, H5, H7) and B viruses . In addition, a combination of oseltamivir and NTZ/TIZ in vitro has a synergistic effect against both human and avian influenza A viruses, including an oseltamivir‐resistant virus . The potential benefit in using a virus‐targeting antiviral (oseltamivir) in combination with the host‐targeting antiviral (NTZ) is the improvement in the effectiveness of influenza treatment as well as the reduction in the likelihood of selecting for resistance.…”
Section: Host Cell Targeting Compoundsmentioning
confidence: 99%